Suzuki cross-coupling and intramolecular aza-michael addition reaction sequence towards the synthesis of 1,10b-epi-7-deoxypancratistatins and their cytotoxicity studies - Pandey, Ganesh; Balakrishnan, Madhesan; Swaroop, Pandrangi Siva (European Journal of Organic Chemistry, 2008)
The development of an efficient approach to the construction of a phenanthridone is described. The convergent strategy commences with the preparation of Suzuki cross-coupling reaction precursors, arylboronic acid 12 and a-iodo enone 14, from piperonylamine (9) and (-)-D-quinic acid (10), respectively. The coupling of 12 and 19 followed by a key intramolecular aza-Michael addition produced phenanthridone 21 featuring a cis-fused B-C ring junction. The syntheses of compounds 25 and 26, both of which are C-1 and C-10b epimers of the naturally occurring potent antitumor agent 7-deoxypancratistatin (2), from 21 are elaborated in detail in this paper. The cytotoxicities of 25 and 26 were evaluated against three different cancer cell lines. Compound 26 served as a moderate growth inhibitor of THP-1 monocytic cells (GI(50) = 14.5 mu g/mL). ((C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008)
Keywords: antitumor agents; Chiral pool; Cross-coupling; Intramolecular aza-Michael addition; Pancratistatin

Antituberculosis agent diaportheone B: synthesis, absolute configuration assignment, and anti-TB activity of its analogues - Swaroop, Pandrangi Siva; Raut, Gajanan N.; Gonnade, Rajesh G.; Verma, Priyanka; Gokhale, Rajesh S.; Reddy, D. Srinivasa (Organic & Biomolecular Chemistry, 2012)
First synthesis of diaportheone B, an antituberculosis agent isolated from endophytic fungus Diaporthe sp. P133 is reported using two complementary routes, a one step and a three-step sequence. The absolute configuration of diaportheone B was determined by using X-ray crystal structure analysis of its dibromo derivative. In addition, we have prepared several close analogues of diaportheone B and determined their anti-TB potential using Alamar-blue assay (H(37)Rv).

Green synthetic route to antimalarial and antibacterial agent CJ-15,801 and its isomer cis-CJ-15,801 - Kashinath, K.; Swaroop, Pandrangi Siva; Reddy, D. Srinivasa (RSC Advances, 2012)
An efficient and rapid synthesis of antiplasmodial and antibacterial agent CJ-15,801 and its isomer cis-CJ-15,801 is disclosed. We have made an attempt towards ``Ideal Synthesis'' or a step towards ``Dial-a-Molecule'' by reducing the number of steps, following atom economy, and a green synthetic route.

Syntheses and determination of absolute configurations and biological activities of the enantiomers of the longtailed mealybug pheromone - Ramesh, Remya; Swaroop, Pandrangi Siva; Gonnade, Rajesh G.; Thirupath, Choppari; Waterworth, Rebeccah A.; Millar, Jocelyn G.; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2013)
Preparation and assignment of absolute configurations to both enantiomers of the sex pheromone of the longtailed mealybug, an irregular monoterpenoid with extraordinary biological activity, has been completed. Comparison of the biological activities of both enantiomers and the racemate in field trials showed that the (S)-(+)-enantiomer was highly attractive to male mealybugs, strongly suggesting that female longtailed mealybugs produce this enantiomer. The (R)-(-)-enantiomer was benign, being neither attractive nor inhibitory.

Efforts towards the synthesis of microsporin B: ready access to both the enantiomers of the key amino acid fragment - Swaroop, Pandrangi Siva; Tripathy, Sibanarayan; Jachak, Gorakhnath R.; Reddy, D. Srinivasa (Tetrahedron Letters, 2014)
Both the isomers methyl-(2S,8R)-2-((tert-butoxycarbonyl)amino)-8-hydroxydecanoate and methyl-(2S,8S)-2-((tert-butoxycarbonyl)amino)-8-hydroxydecanoate of an unusual amino acid residue and the key fragment of microsporin B are prepared. The key steps include cross metathesis and enzymatic kinetic resolution. In addition, a linear tetrapeptide with desired components towards total synthesis is also reported. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Cross metathesis; Enzymatic resolution; HDAC inhibitor; Microsporin; Tetrapeptide